Talassoterapia para pacientes com fibromialgia: ensaio clínico radômico - Andrade, Sandra Cristina de (2008)
Fibromyalgia (FM) is a chronic rheumatic syndrome characterized by diffuse muscle-skeletal pain, and aerobic exercises represent a fundamental portion in therapeutic approach. Objective of this study was to evaluate the effectiveness of aerobic exercises accomplished in the water of the sea (thalassotherapy) for women with FM and to compare with exercises accomplished in the swimming pool, involving a multidisciplinary team, composed by rheumatologists, physical therapists, students of physical therapy and students of physical education. Forty six (46) women with age between 18 and 60 years with FM were randomized in 2 groups: a swimming pool group (23 patients) and a sea group (23 patients). 80th groups trained a week with the same program of aerobic conditioning 3 times (60 minutes each) for 12 weeks. Ali the patients were evaluated, before and immediately after treatment, with Visual Analogical Scale (VAS) for pain and fatigue, number of tending points, Fibromyalgia Impact Ouestionnaire (FIO), Short Form 36 Health Survey (SF-36), Pittsburgh Sleep Ouality Index (PSOI) and Beck Oepression Inventory (BOI). For statistical analysis, it was used paired-t test for analysis intra-group and non-paired test for inter-groups analysis, significance levei of p <0,05. Four patients, of each group, didn't complete the training programo Groups were homogeneous and they were compared in initial evaluation, except for BOI (p <0,05). Both groups presented statistically significant improvement for ali appraised parameters in the post-treatment compared with initial evaluation, there were reduction of intensity of pain and fatigue, number of tending points, better functional capacity (FIO), life quality (SF-36), quality of sleep (PSQI) and depression indexes (BOI). However, in comparison among the groups, group of sea (thalassotherapy) presented better results for ali parameters, however with statistically significant difference just only for depression indexes (BOI). At the end, it was observed that accomplishment of aerobic exercises in sea water or swimming pool was effective as part of treatment for patients with FM. However, exercise programs with thalassotherapy seems to bring more benefits, mainly related to emotional aspects, could be a therapeutic option of low cost for patients with FM in our area